Exploring indigenous wisdom: Ethnobotanical documentation and conservation of medicinal plants in Goba District, Southwest Ethiopia - Ginjo Gitima; Ashenafi Gebre; Yericho Berhanu; Tamirat Wato (Scientific African)
Understanding the community's knowledge and reliance on plant based traditional medicine is crucial for creating effective, sustainable conservation strategies to protect and preserve these valuable plant resources. This study aimed to explore traditional medicinal plants and the associated indigenous knowledge in the study area. Ethnobotanical data were collected from January to April 2024 using semistructured interviews and guided field observations. Data on medicinal plants and demography were gathered from 99 respondents, including 83 general informants and 16 key informants. A total of 115 medicinal plant species across 44 families were documented. The Asteraceae family was the most represented (11.3%), and the majority of the collected medicinal plants were herbs (52.2%). Leaves were the most frequently used plant parts (57.4%), and oral administration was the predominant route (74.78%). Ocimum lamiifolium Hochst.,emerged as the most effective medicinal plant for treating severe headaches (''Micho'') and received the highest fidelity level (97%). The highest informant consensus factor (ICF) was for gastrointestinal diseases (0.92). Furthermore, Croton macrostachyus ranked first as the most versatile multipurpose plant. These findings highlights the critical role of traditional knowledge in local healthcare systems and the importance of sustainable plant utilization. Respondents unanimously (100% agreement) identified firewood collection, population growth, and lack of awareness and education as major threats to medicinal plants.. This study emphasizes the crucial role of traditional medicinal plants in the healthcare practices of communities and the urgent need for sustainable conservation measures to conserve these invaluable resources and indigenous knowledge for the long-term benefit of both human health and biodiversity conservation.